There is no global running pattern more economic than another at endurance running speeds - Patoz, A.; Lussiana, T.; Breine, B.; Gindre, C.; Hébert-Losier, K. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The subjective Volodalen® score (V®score) and the objective duty factor metric can both assess global running patterns. The authors aimed to investigate the relation between running economy (RE) at endurance running speeds and the global running pattern quantified using both subjective and objective measures.